Papua in Media: A Discourse Critical Analysis of Economic News in Three National Indonesian Newspapers - Sari, Mungky Diana (Bina Nusantara University, 2016)
For so many years, peace in Papua has become a high critical thing in Indonesian politics. In order to find the solution, the paradigm has been shifted from security to welfare or economic approach. Article explored the impact of religion affiliation toward news making and news frame, especially in economic news published by mass media. This research was developed to explore the framing formed by three media outlets which each of them affiliated with certain religion. This research focused on the analysis of economic articles published by three media outlets; Sinar Harapan, Republika, and Kompas daily. The method of framing analysis was based on Robert N. Entman theory, while the critical discourse analysis method was based on Norman Fairclough theory. Political economics theories such as Vincent Mosco, Robert E. Babe, and D.W. Smythe to analyze the influence of religion affiliation in news production were also used. Meanwhile, some political communication theories such as Brian McNair, Dann Nimmo, Noam Chomsky and Denis McQuail were also used to know how media stands in Papua conflict. From the research, it is discovered that the religion affiliation has a big impact on news media and its content, and also the frame that is built. Not only political-economic matters, but